Respons Hematologi dan Kimia Darah Domba Lokal Indonesia Terhadap Stres Transportasi Selama 12 Jam (HAEMATOLOGICAL AND BLOOD BIOCHEMICAL RESPONSES TO 12 HOUR TRANSPORTATION STRESS IN IN LOCAL INDONESIAN SHEEP) - Sarmin, Sarmin; Hana, Amelia; Astuti, Pudji; Febrianto, Yuda Heru; Airin, Claude Mona (Jurnal Veteriner; Vol 20 No 1 (2019), 2019)
The objective of this study was to investigate the effect of transport 12 hours on  haematological and some biochemical responses of local Indonesian sheeps.  Ten adults (2.0-2.5 years)  male local Indonesian sheeps  BW adult 30-40 kg were transported by L-300 pickup truck starting at 3:00 pm to 3:00 am on the d 2 without stopping. Jugular blood were collecte-d at 7 am (-8 h pre- transportation as baseline), 15:00  immadiately after (0 h),  19:00 (4 h), 23:00 (8 h) ,  03.00 (12 h ), and at 11.00 d 2 (+8 h)  post-  transportation as recovery period). Under  the conditions of the present study, transport of local Indonesian sheeps significantly increased glucose  during 4 h  transport (P <0.05), increased eosinophil at 0 h (P <0.05) and no significant changed in erythrocytes, haemoglobin , monocytes, neutrophils, lymphocytes, leukocytes,  packed cell volume (PCV), and total plasma protein (TPP) (P> 0.05). Our findings showed that transportation 12 h affected  eosinophil during 0 h and glucose metabolism during 4 h of transportation, but did not any affect on some haematology and dehydration responses in local Indonesian sheeps.